2011
DOI: 10.1002/cpa.20367
|View full text |Cite
|
Sign up to set email alerts
|

An optimal family of exponentially accurate one‐bit Sigma‐Delta quantization schemes

Abstract: Sigma-delta modulation is a popular method for analog-to-digital conversion of bandlimited signals that employs coarse quantization coupled with oversampling. The standard mathematical model for the error analysis of the method measures the performance of a given scheme by the rate at which the associated reconstruction error decays as a function of the oversampling ratio . It was recently shown that exponential accuracy of the form O.2 r / can be achieved by appropriate one-bit sigma-delta modulation schemes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
87
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(88 citation statements)
references
References 18 publications
1
87
0
Order By: Relevance
“…Here C 1 < 1 is a small constant 1 . This work was improved on by Deift et al [5], who showed that the above constant can be pushed to C 1 ≈ 0.102. In order to achieve exponential precision, these works use stable families of r-th-order Σ∆ schemes with approximation errors bounded by C 2 (r)λ −r .…”
Section: B σ∆ Quantization Of Oversampled Bandlimited Functionsmentioning
confidence: 90%
See 4 more Smart Citations
“…Here C 1 < 1 is a small constant 1 . This work was improved on by Deift et al [5], who showed that the above constant can be pushed to C 1 ≈ 0.102. In order to achieve exponential precision, these works use stable families of r-th-order Σ∆ schemes with approximation errors bounded by C 2 (r)λ −r .…”
Section: B σ∆ Quantization Of Oversampled Bandlimited Functionsmentioning
confidence: 90%
“…In this note, we combine the techniques of Blum et al [8] and Güntürk [4]/Deift et al [5] to show that it is possible to achieve root-exponential accuracy in the finite frame setting. In particular, we show that for a family of tight frames of special design that admit themselves as Sobolev duals, and for harmonic frames, root-exponential error rates of O(e −C √ λ ) are achievable.…”
Section: σ∆ Quantization Of Finite Frame Expansionsmentioning
confidence: 99%
See 3 more Smart Citations